Diversification and Branding of Water Hyacinth Products in Wotgalih Village, Lumajang Regency - Ifa, Khoirul; Robustin, Tri Palupi; Lukiana, Ninik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
The Beginner Community Service Program (PMP) was carried out in Wotgalih Village, Lumajang, with a focus on empowering water hyacinth artisans to improve the creative economy based on local resources. Water hyacinth, which has been considered an aquatic weed, is used to produce handicraft products such as bags, sandals, hats, and household accessories, adding economic value. However, artisan businesses still face significant obstacles, including limited product diversification, reliance on traditional production technologies, and limited marketing strategies. The solutions offered include product design innovation training, the procurement of appropriate technology, such as zigzag sewing machines, to improve production efficiency, and branding and digital marketing assistance through social media. The implementation method includes socialization, training, technology application, intensive mentoring, and sustainability evaluation. The expected results include creating at least 5 new product types with modern designs, strengthening artisans' skills, and forming brand identities and digital marketing networks capable of penetrating local, national, and international markets. This program not only contributes to improving people's welfare but also supports the achievement of the SDGs, especially in poverty alleviation, decent work and economic growth, sustainable consumption and production, and the preservation of aquatic ecosystems. Thus, using water hyacinth as an innovative craft can be a strategic solution to reduce environmental impact while strengthening the village's creative economy.